Research on Key Techniques of the Verification and Testing System for Spacecraft Propulsion - Junwei Wang; Lei Zhang; Qingsheng Xiao; Gao Li; Xiao Han; Bing Bai (MATEC Web of Conferences, 2018)
Electric propulsion is an important technology in the future space missions. The verification and testing system is mainly used for the manufacturers to fully understand the propulsion behavior in the most diverse conditions, and to indentify and eliminate potential failure modes to advance its validity and reliability, explore the applied potential for space missions. The paper presents a new verification and testing system for spacecraft propulsion and the key technologies needed to be developed are studied. The debugging data and research indicate that ultimate pressure of system is better than the 5.0×10-6Pa. Both the cold plate used for xenon pumping and sputtering protective system get an excellent performance in system. The DSMC numerical simulation method is verified that is beneficial to the research of optimization design and plume effect of electric propulsion in future.